Blood Pressure in De Novo Heart Transplant Recipients Treated With Everolimus Compared With a Cyclosporine-based Regimen: Results From the Randomized SCHEDULE Trial. Issue 4 (April 2019) - Andreassen, Arne K.; Broch, Kaspar; Eiskjær, Hans; Karason, Kristjan; Gude, Einar; Mølbak, Dorte; Stueflotten, Wenche; Gullestad, Lars
Abstract : Background: Systemic hypertension is prevalent in heart transplant recipients and has been partially attributed to treatment with calcineurin inhibitors (CNIs). SCandinavian HEart transplant De-novo stUdy with earLy calcineurin inhibitors avoidancE trial was the first randomized trial to study early withdrawal of CNIs in de novo heart transplant recipients, comparing an everolimus-based immunosuppressive regimen with conventional CNI-based treatment. As a prespecified secondary endpoint, blood pressure was repeatedly compared across treatment arms. Methods: The The SCandinavian HEart transplant De-novo stUdy with earLy calcineurin inhibitors avoidancE trial was a prospective, multicenter, randomized, controlled, parallel-group, open-label trial in de novo adult heart transplant recipients, undertaken at transplant centers in Scandinavia. Blood pressure was assessed with 24-hour ambulatory blood pressure monitoring up to 3 years after heart transplantation (HTx) in 83 patients. Results: Overall, systolic blood pressure fell with time, from 138 ± 15 mm Hg 2 weeks after HTx to 134 ± 11 mm Hg after 12 months and 132 ± 14 mm Hg after 36 months ( P = 0.003). Diastolic blood pressure did not change over time. After 12 months, there was a numerically larger fall in systolic blood pressure in the everolimus arm (between-group difference 8 mm Hg; P = 0.053), and after 36 months, there was a significant between group difference of 13 mm Hg ( P = 0.02) in favor of everolimus. Conclusions: In this first, randomized trial with early CNI avoidance in de novo HTx recipients, we observed a modest fall in systolic blood pressure over the first 1 to 3 years after transplantation. The fall in systolic blood pressure was more pronounced in patients allocated to everolimus. Abstract : Supplemental Digital Content is available in the text.